2021
DOI: 10.1111/ejn.15240
|View full text |Cite
|
Sign up to set email alerts
|

Common and distinct neural trends of allocentric and egocentric spatial coding: An ALE meta‐analysis

Abstract: The uniqueness of neural processes between allocentric and egocentric spatial coding has been controversial. The distinctive paradigms used in previous studies for manipulating spatial coding could have attributed for the inconsistent results. This study was aimed to generate converging evidence from previous functional brain imaging experiments for collating neural substrates associated with these two types of spatial coding. An additional aim was to test whether test‐taking processes would have influenced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 76 publications
(155 reference statements)
0
10
0
Order By: Relevance
“…Several studies have reported the activation in areas of the ventrolateral occipito-temporal cortex, such as the occipital 9 , 10 , 29 , 33 and lateral temporal cortices 10 , 33 , during an egocentric judgment task. Furthermore, a recent meta-analysis using activation likelihood estimation (ALE) has shown the specific involvement of the right middle occipital gyrus to egocentric spatial judgment but not to allocentric judgment 34 . The present results support this finding and suggest a specific contribution of the right middle occipital gyrus to egocentric spatial coding.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the activation in areas of the ventrolateral occipito-temporal cortex, such as the occipital 9 , 10 , 29 , 33 and lateral temporal cortices 10 , 33 , during an egocentric judgment task. Furthermore, a recent meta-analysis using activation likelihood estimation (ALE) has shown the specific involvement of the right middle occipital gyrus to egocentric spatial judgment but not to allocentric judgment 34 . The present results support this finding and suggest a specific contribution of the right middle occipital gyrus to egocentric spatial coding.…”
Section: Discussionmentioning
confidence: 99%
“…The parieto-premotor pathway is involved in eSC, and its core neural substrates are the cIPL, superior parietal lobule (SPL; including IPS), somatosensory motor area (SMA), and FEF (1,28,29). IPS is related to attention and FEF is related to the action template formations (7,18,30). The parieto-medial temporal pathway, on the other hand, is involved in aSC (1), and its key neural substrates are the caudal part of IPL (area PG) (31,32), PCC (33), the retrosplenial cortex (RSC), temproparietal junction (TPJ), and medial temporal lobule (MTL) (34,35).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is thought to be critically involved in the translation of information between allocentric (world-centred) and egocentric (self-centred) spatial reference frames 48,49,61,[65][66][67][68][69] . Relatedly, the precuneus is thought to play a role in developing and maintaining concurrent egocentric and allocentric spatial reference frames 48,70 . There is also evidence to suggest that the posterior cingulate and retrosplenial cortex both contribute to our sense of selflocation, with the posterior cingulate being particularly involved in the integration of neural representations of self-location and body ownership 71 .…”
Section: Vection-consistent Versus Vection-inconsistent Visual Motion...mentioning
confidence: 99%